Pengaruh Promosi Penjualan Sabun Leivy terhadap Keputusan Pembelian pada Konsumen CV. Kiano Sukses Mandiri Kota Jambi - Muhammad Raihan Mubaraq (Universitas Batanghari Jambi, 2019)
This researchdiscusses the sales promotion of purchasing decisions on CV. Kiano Sukses Mandiri Jambi City. The object of this research is CV. Kiano Sukses Mandiri Jambi City Period 2013-2017. The type of data in this research uses primary data and secondary data, it can be used using questionnaires and such as literature books, newspapers, magazines, and information relating to the problem being discussed. The population in this research were all consumers of CV. Kiano Sukses Mandiri Jambi City in 2017 was 554. The sample in this research was 100 people. By using descriptive qualitative methods and quantitative descriptive methods. The analysis tool that uses Simple Linear Regression Equations with the support by SPSS 20.0 software besides that is also tested Classical assumptions and hypothetical test to determine the significance of independent variables on variables using F Test, t Test and Test of determination. Based on the results of the research examining this research meets the requirements in the classic assumption test. Based on hypothetical testthe value of T count on the Sales Promotion variable (X) is 5.614 with a significance level of 0.000. Because the value of t count is 5.614> the value of t table is 1.984 and the significance level is 0.000 <probability of significance a = 0.1. then Ho refused Ha accepted. This means that the Promotion Sales variable individually has a positive and significant effect on the Purchase Decision Conclusions Based on thisresearch Sales Promotion on Leivy soap products from 100 respondents the score is 309.65 and belongs to the category of